HUBUNGAN ANTARA KETERAMPILAN KERJA DENGAN TINGKAT PRODUKTIVITAS KERJA KARYAWAN PADA PT. PEC TECH SERVICE INDONESIA SEKTOR TESO BARAT KABUPATEN PELALAWAN - Aqsa, Muhammad Ali (Eko dan Bisnis: Riau Economic and Business Review, 2018)
This research was conducted at PT. Pec Tech Service Indonesia West Sector Of Teso. With the aim of this study is to find out how big the relationship between skill work with employee productivity.Determination of the sample in this research is to use the sample slovin approach so obtained in this study is as much as 56 people respondents.Methods of data analysis that is used is to use the simple correlation method with coefficients of spearman rank through determination.Based on the test results, the correlation of test results obtained 0.827, so it can be inferred, there is a very strong relationship and positive between job skills with work productivity employees employee at PT. Pec Tech Service Indonesia West Sector Of The Teso